Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s11130-013-0389-2
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Bioavailability of Antioxidant Phytochemicals and Increase of Serum Oxidation Resistance in Healthy Subjects Following Supplementation with Raisins

Abstract: The aim of this study was to examine the postprandial impact of raisin supplementation in serum resistance to oxidation of healthy subjects, to quantify the bioavailable phenolic compounds and oleanolic acid. The content of phytochemicals in raisins was determined by GC-MS. Fifteen healthy volunteers who consumed 144 g of raisins were subjected to blood collection at time 0 and 1, 2, 3 and 4 h after consumption. Blood samples were used for the quantification of (a) serum oxidizability (b) plasma total polyphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 18 publications
0
33
0
1
Order By: Relevance
“…oxLDL in blood is considered the most specific biomarker for oxidative stress evaluation in humans; most recently its measurement applying immunological methods (i.e., antibodies) has been recognized by European Food Safety Authority as a reliable method to assess oxidative damage with appropriate specificity. [23] It is also important to mention that in the study of Kanellos and colleagues, [22] a total of 17 phytochemicals were identified and quantified in plasma including oleanolic acid (a pentacyclic triterpenoid), but also phenolic compounds such as vanillic acid, gallic acid, tyrosol, and quercetin, that have been previously identified in Mastiha as well. Each compound followed a different kinetic pathway, nevertheless 13 of 17 phytochemicals peaked in plasma 1 h after administration.…”
Section: Discussionmentioning
confidence: 99%
“…oxLDL in blood is considered the most specific biomarker for oxidative stress evaluation in humans; most recently its measurement applying immunological methods (i.e., antibodies) has been recognized by European Food Safety Authority as a reliable method to assess oxidative damage with appropriate specificity. [23] It is also important to mention that in the study of Kanellos and colleagues, [22] a total of 17 phytochemicals were identified and quantified in plasma including oleanolic acid (a pentacyclic triterpenoid), but also phenolic compounds such as vanillic acid, gallic acid, tyrosol, and quercetin, that have been previously identified in Mastiha as well. Each compound followed a different kinetic pathway, nevertheless 13 of 17 phytochemicals peaked in plasma 1 h after administration.…”
Section: Discussionmentioning
confidence: 99%
“…Bioavailability is the proportion of a compound that enters the systemic circulation when introduced into the body. Experimental and clinical studies reported the presence of oleanolic acid in blood several hours after intake in its intact form [39,40,41], but oral bioavailability was low due to low aqueous solubility and intensive metabolism by cytochrome P450 isoenzymes (CYP) [42]. Jeong et al [43] reported that the bioavailability of oleanolic acid after oral administration was only 0.7% in rats.…”
Section: Sources and Bioavailabilitymentioning
confidence: 99%
“…as assessed by the FRAP assay, plasma TRAP values were not altered in a study by Barnes et al 21 The quantity of the bioavailable phenolic compounds in raisins has been assessed by Kanellos et al 22 Fifteen healthy volunteers consumed 144 g of raisins followed by blood collection at 0 and 1, 2, 3 and 4 hours post consumption. Twenty-five phytochemicals were identified and quantified in raisins; oleanolic acid, a triterpenoid, was found in the highest concentration.…”
Section: / Raisins and Their Relationship To Human Healthmentioning
confidence: 98%